Clinical significance and cytological detection of tracheal puncture following thyroid fine‐needle aspiration: A retrospective study. Issue 10 (21st July 2021) - Tanaka, Aki; Hirokawa, Mitsuyoshi; Suzuki, Ayana; Higuchi, Miyoko; Kanematsu, Risa; Yamao, Naoki; Kuma, Seiji; Hayashi, Toshitetsu; Miyauchi, Akira
Abstract: Background: There have been no detailed reports on tracheal puncture after thyroid fine‐needle aspiration (FNA). This study aimed to discuss the cytological differential diagnoses of tracheal puncture after thyroid FNA and clarify its clinical significance. Methods: Tracheal puncture was defined as aspiration of tracheal components, including ciliated cells, chondrocytes, and goblet cells. A history of air suction or cough during aspiration was also considered tracheal puncture. Among the 18, 480 nodules from 13, 813 patients that underwent thyroid FNA, 70 (0.38%) nodules with tracheal puncture were retrospectively examined. Eleven thyroglossal duct cysts (TGDCs) and seven bronchial cysts that could exhibit ciliated cells were included in the study to compare the cytological findings. Results: Sixty‐six (94.3%) nodules had no clinical evidence of complications during and after FNA. Of the nodules with tracheal puncture, 64.3%, 48.6%, and 51.4% nodules were <1.0 cm in size, located in the isthmus, and associated with calcification. Cytological examination showed that chondrocytes and ciliated cells were present in 94.3% and 32.9% nodules, respectively. Ciliated cells seen in nodules with tracheal puncture and TGDCs were non‐degenerative, whereas those in bronchial cysts were degenerative. Conclusion: Tracheal puncture after thyroid FNA is rarely noticed clinically, does not cause serious conditions, and spontaneously resolves. This complication more likely occurs in small‐calcified nodules in the isthmus. Chondrocytes are more reliable diagnostic clues than ciliated cells to indicate tracheal puncture cytologically.